Apparent Diffusion Coefficient to Evaluate Adult Intracranial Ependymomas: Relationship to Ki‐67 Proliferation Index. Issue 1 (22nd September 2020) - Xianwang, Liu; Lei, Han; Hong, Liu; Juan, Deng; Shenglin, Li; Caiqiang, Xue; Yan, Hao; Junlin, Zhou
ABSTRACT: BACKGROUND AND PURPOSE: There are important differences in the treatment and prognosis of adult intracranial low‐grade ependymomas (grade II) versus anaplastic ependymomas (grade III). We evaluated the value of the apparent diffusion coefficient (ADC) for differentiating these two tumors and further investigated the relationship between ADC values and the Ki‐67 proliferation index. METHODS: Clinical and preoperative magnetic resonance imaging data of 35 cases of adult intracranial ependymomas were retrospectively analyzed, including 20 low‐grade ependymomas and 15 anaplastic ependymomas. The minimum ADC (ADCmin), average ADC (ADCmean), and normalized ADC (nADC) were compared between the two groups. Receiver operating characteristic curves were drawn to evaluate the differentiating accuracy of ADC values. The Ki‐67 proliferation index of the solid tumor components was also measured to explore its relationship with ADC values. RESULTS: The ADCmin (.89 ± .17 vs. .66 ± .09 × 10 −3 mm 2 /second), ADCmean (.98 ± .21 vs. .72 ± .11 × 10 −3 mm 2 /second), and nADC (1.38 ± .31 vs. 1.02 ± .18 × 10 −3 mm 2 /second) were significantly higher in adult intracranial low‐grade ependymomas than anaplastic ependymomas cases (all P < .05). ADCmean best distinguished the two groups, with an area under the curve value of .900. Using .716 × 10 −3 mm 2 /second as the optimal threshold, the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of the two groups were 66.7%, 100%, 85.7%, 100%, and 80%, respectively. ADCmin ( r = −.490), ADCmean ( r = −.449), and nADC ( r = −.425) showed significant negative correlations with the Ki‐67 proliferation index (all P < .05). CONCLUSIONS: ADC values can differentiate adult intracranial low‐grade ependymomas and anaplastic ependymomas, which could improve the preoperative diagnostic accuracy of these two tumors and guide their treatment.